Dielectric/Semiconductor Interfacial p-Doping: A New Technique to Fabricate Solution-Processed High-Performance 1 V Ambipolar Oxide Transistors - Chourasia N.K.; Sharma A.; Pal N.; Biring S.; Pal B.N. (My University, 2025)
Herein, dielectric/semiconductor interfacial p-doping is used to develop a high-carrier-mobility and balanced ambipolar tin oxide (SnO2) thin-film transistor (TFT). To introduce this interfacial doping, TFTs are fabricated by using two different ion-conducting oxide dielectrics containing trivalent atoms. These ion-conducting dielectrics are LiInO2 and LiGaO2 containing a mobile Li+ ion that reduces the operating voltage of these TFTs to ≤2.0 V. During SnO2 thin film deposition, the interfacial SnO2 layer is p-doped by an In or Ga atom of the gate dielectric and therefore, hole conduction is facilitated in the channel of the TFT. To realize this interfacial doping phenomenon, a reference TFT is fabricated with a Li2ZnO2 dielectric that contains a divalent zinc atom. Comparative electrical data indicate that TFTs with LiInO2 and LiGaO2 dielectrics are ambipolar in nature, whereas the TFT with a Li2ZnO2 dielectric is a unipolar n-channel transistor, corroborating the interfacial doping of SnO2. Most interestingly, using a LiInO2 dielectric, a 1.0 V balanced ambipolar TFT with high electron and hole mobility values of 7 and 8 cm2 V−1 s−1, respectively, can be fabricated, with an on/off ratio > 102 for both operations. The TFT with a LiInO2 dielectric is utilized successfully to fabricate a low-voltage complementary metal–oxide–semiconductor (CMOS) inverter. © 2020 Wiley-VCH GmbH